2008
DOI: 10.1021/la702284b
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Cell Surface and Cell Wall Chemistry of Drinking Water Bacteria by Combining XPS, FTIR Spectroscopy, Modeling, and Potentiometric Titrations

Abstract: Aquabacterium commune, a predominant member of European drinking water biofilms, was chosen as a model bacterium to study the role of functional groups on the cell surface that control the changes in the chemical cell surface properties in aqueous electrolyte solutions at different pH values. Cell surface properties of A. commune were examined by potentiometric titrations, modeling, X-ray photoelectron spectroscopy (XPS), and Fourier transform infrared (FTIR) spectroscopy. By combining FTIR data at different p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
137
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(149 citation statements)
references
References 61 publications
12
137
0
Order By: Relevance
“…The reported spectral changes point to the deprotonation of the carboxyl group [6]. Similar correlations were observed by Ojeda in Aquabacteriumcommune and by Leonea in Bacillus subtilis [18,22]. Changes ascribed to symmetric (ν=1100 cm -1 ) and asymmetric (ν=1220 cm -1 ) stretching vibrations P=O (ν P=O ) of phosphate groups were also observed in the region of ν=1100-1220 cm -1 .…”
Section: Ftir Spectroscopysupporting
confidence: 80%
See 2 more Smart Citations
“…The reported spectral changes point to the deprotonation of the carboxyl group [6]. Similar correlations were observed by Ojeda in Aquabacteriumcommune and by Leonea in Bacillus subtilis [18,22]. Changes ascribed to symmetric (ν=1100 cm -1 ) and asymmetric (ν=1220 cm -1 ) stretching vibrations P=O (ν P=O ) of phosphate groups were also observed in the region of ν=1100-1220 cm -1 .…”
Section: Ftir Spectroscopysupporting
confidence: 80%
“…On the other hand, this region is characteristic for vibration of hydroxyl groups coming from water. Therefore, for evaluation obtained spectra is important range of ν = 500 -2000cm-1 [18]. In particular, the bands at ν = 1450 -1456cm−1 and ν = 1385 -1392cm−1 may be attributed to deprotonated carboxyl groups (COO−) of bacterial peptides (mostly asparagine and glutamine residues).…”
Section: Ftir Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…31,[44][45][46] In addition, several studies have recently attempted to characterize the chemistry of cell membrane or polymeric layers by combining macroscopic (e.g., zeta potential, surface hydrophobicity, potentiometric titration) and molecular (e.g., scanning electron microscopy, transmission electron microscopy, Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy) techniques. [47][48][49] However, it is still not straightforward to quantify and generalize macromolecule-related variations in cell surface properties due to the complexity of the cell surface and the sensitivity of macromolecules to the cell type (e.g., species, serotypes, or strains) 19,35,50 and environmental conditions (e.g., growth stage, temperature, and solution chemistry). 15,19,20,51 Our recent studies 32,38,52 showed that the deposition behavior of E. coli O157:H7 in porous media could not be explained by traditional approaches (i.e., classic DLVO theory 23,24 and filtration theory 53 ) and indicated that the presence of macromolecules on the cell surface likely influenced their surface characteristics and adhesion behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Fourier transform infrared spectroscopy (FT-IR) was applied to characterize changes in yeast cell wall structure [17][18][19]. This method has been extensively used in recent years for the study of microbial surfaces, and the identification and classification of microorganisms [20][21][22][23].…”
Section: Abstract: Ft-ir Spectroscopy • Lithium • Saccharomyces Cerevmentioning
confidence: 99%